Peningkatan Pembelajaran Sifat-sifat Bangun Ruang Berorientasi Teori Van Hiele di Kelas V SD - Oktaviani, Rike; Zainil, Melva; F, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of the study was to describe the planning, the implementation, and the increase of the learning outcome of geometry characteristics oriented to Van Hiele theory in the fifth grade of Public Elementary School number 11 Indarung of Padang. The type of the study was a clasroom action research using qualitative and quantitative approach. The subjects of the study were the teacher and the 23 students. The result of the study showed that there  was an enhancement from cycle I to cycle II as following: (a) the planning in cycle I increased by 10,7% in cycle II, (b) the implementation of the teacher and the students aspects in cycle I increased by 15% in cycle II, (c) the learning outcome in cycle I increased by 10,5 in cycle II.Key words: geometry characteristics, Van Hiele theory